What Is the Role of AI in Sleep Disorder Assessment? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2016)
Sleep disorders affect a significant portion of the global population, with estimates suggesting that 30-45% of adults experience sleep-related issues [1]. T...
Keywords: AI in Mental Health; Sleep; Disorder; Assessment; Artificial Intelligence; Machine Learning; Deep Learning